1970
DOI: 10.1113/jphysiol.1970.sp009174
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intragastric hyperosmolal solutions on gastric functions

Abstract: SUMIARY1. The effects of intragastric hyperosmolal solutions on resting and secreting stomachs of anaesthetized cats have been studied.2. Hyperosmolal solutions reduced acid secretion in response to histamine and gastrin. There was a significant correlation between increase in osmolality and decrease in acid response to small doses of gastrin. A continuous acid secretion produced by large doses of gastrin was not significantly reduced.3. The loss of H+ from resting stomachs is related to the pH and osmolality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1971
1971
1989
1989

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…2A) was similar to that observed between H+ loss and instilled pH when no NaF was present in the instilled solution, but more acid was lost at any one pH value under the influence of NaF. A similar increased H+ loss at any one pH value has been observed under the influence of hyperosmolal solutions (Harper, Reed & Smy, 1970). This evidence alone indicated the possibility that in non-stimulated stomachs NaF solutions, as seemed likely with hyperosmolal solutions, enhanced a H+ loss mechanism in the non-fluoride exposed stomach which was not associated with a Na+ exchange.…”
Section: Non-acid Secreting Stomachssupporting
confidence: 82%
“…2A) was similar to that observed between H+ loss and instilled pH when no NaF was present in the instilled solution, but more acid was lost at any one pH value under the influence of NaF. A similar increased H+ loss at any one pH value has been observed under the influence of hyperosmolal solutions (Harper, Reed & Smy, 1970). This evidence alone indicated the possibility that in non-stimulated stomachs NaF solutions, as seemed likely with hyperosmolal solutions, enhanced a H+ loss mechanism in the non-fluoride exposed stomach which was not associated with a Na+ exchange.…”
Section: Non-acid Secreting Stomachssupporting
confidence: 82%
“…As shown in a recent study, acid secretion of the in vitro frog fundic mucosa also decreased markedly after exposure to 1 M NaCI [27], Rehm et al [18] observed that hypertonic solutions of 2-4 M NaCI and NaNOi decreased histamine-stimulated acid secretion in chambered portions of rat fundic mucosa with intact blood supply. Harper et al [9] showed that gastric installation of hy perosmolar glycine and mannitol solutions (383-1,095 mosm kg-1) reduced acid secre tion in response to histamine and gastrin in cats. Rollin et al [20] have found that hyper osmotic glucose added to the mucosal side of isolated chambered rat fundic mucosa caused a marked reduction of acid secretion.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of a hydrogen ion chemoreceptor in the duodenum is in no way antagonistic to the findings of Hunt and Knox [1969]. Apart from the fact that their work was on the gastric emptying of unanaesthetized man, and not on the nerve responses in the duodenum of anaesthetized rabbits, it has been shown that acid in the stomach can evoke nervous [Iggo, 1957;Williams and Forrest, 1969], humoral [Shimizu et al, 1958;Elwin, 1968] and local cellular responses [Harper, Reed and Smy, 1970], and as gastric emptying is possibly controlled by several mechanisms, direct comparison of the two studies would appear to be impossible.…”
Section: Differentiation Of Elicited From Spontaneous Action Potentialsmentioning
confidence: 99%